A comparative study on the healing of incised wound made by surgical knife - Soriano, Yolanda C.; Baltazar, Cecilia M.
This paper is a comparative study of the two methods of incision - the scalpel blade incision and electro surgical incision. A lot of investigations were done to answer questions concerning the histologic effects on tissues. Different studies were done on animals. Its concluded that soft tissue healing in electro surgery and scalpel incision occur at the same rate and there are minor histologic differences between the two methods that can be overlooked. There are also the advantages in using the electro surgery unit.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Electrosurgery; Incisors -- Wounds and injuries